Integration of Religious Values in Public Ethics in a Multicultural Society - Pipit Afrianti; Desie Andreastuti (Journal of Religion and Social Transformation, 2024)
This article aims to describe the relevance of integrating religious values into public codes of ethics to drive social transformation within a multicultural society. Utilizing a narrative review method of previous literature, the article identifies the potential of religious moderation and local cultural values, such as gotong royong (mutual cooperation), as foundational elements to strengthen public ethics. The findings indicate that the application of religion-based public ethics in Indonesia has had a positive impact, including enhancing integrity, reducing corruption, and increasing public awareness of the importance of ethics in public life. Integration of religious values into public ethics holds significant potential to address social challenges in a diverse society like Indonesia. In conclusion, by harmonizing religious principles with cultural norms, public ethics can serve as a unifying framework that promotes inclusivity, accountability, and social harmony, thereby fostering a more just and ethical society